ASSIMILATION OF CONNECTED SPEECH: STUDENTS’ CHALLENGES IN LEARNING PRONUNCIATION - Fitriani (Esteem Journal of English Education Study Programme, 2025)
Pronunciation plays a vital role in effective communication, ensuring that a speaker's message is clearly conveyed to the listener. This research explores the challenges faced by EFL students in pronouncing assimilation in English connected speech, particularly focusing on difficulties with various types of assimilation, including /t/, /d/, /n/, and /s/. An exploratory quantitative approach was utilized, involving students from the English Education Department at STAIN Mandailing Natal. Participants completed a pronunciation test to evaluate their ability to identify and produce assimilated sounds. The results revealed notable difficulties, with a high frequency of incorrect responses, indicating significant challenges in pronouncing certain types of assimilation. Among these, the assimilation of /d/ and /n/ sounds proved to be the most challenging, while /s/ assimilation was comparatively easier. The study emphasizes the importance of targeted pronunciation training, addressing the most problematic assimilation patterns, and integrating interactive, personalized teaching methods to enhance students' overall pronunciation skills.